POTENSI PENURUNAN KONSENTRASI LOGAM BERAT TEMBAGA (CU) DAN PERTUMBUHAN MIKROALGA SPIRULINA PLANTESIS PADA MEDIA KULTUR - Mochamad Rendy Sety0 Budi; Boedi Setya Rahardja; Endang Dewi Masithah (Universitas Sriwijaya, 2018)
ABSTRACT Water is an important environmental component for life. Heavy metal water pollution comes from many industries. Heavy Metals Copper (Cu) is one of several other heavy metals that are harmful to living things. One way to anticipate the increased pollution of heavy metals Copper (Cu) in waters is bioremediation using microalgae. This study aims to determine the ability of Spirulina plantesis in absorbing heavy metals Copper (Cu) and to determine the influence of heavy metal Copper (Cu) on the growth of Spirulina platensis. This study used an experimental method with Completely Randomized Design (RAL) consisting of four treatments and five replicates, namely A (S. platensis 0 ppm), B (S. platensis 1 ppm), C (S. platensis 3 ppm), D (S. Platensis 5 ppm). The results showed that Spirulina platensis was able to absorb heavy metal of Copper (Cu) so that it can be used as a heavy metal bioremediation agent. On treatment B (1 ppm) absorption of 87,719%, C (3 ppm) equal to 97,886% and D (5ppm) equal to 95,872 % Growth with the addition of Cu affects Spirulina platensis growthKeywords: Bioremediation, Spirulina platensis, Copper, Growth